Pd-Cu diatomic catalyst as well as preparation method and application thereof

Through the combination of in-situ XAFS-electrochemical combination technology and Pd-Cu diatom catalyst, the electrochemical reaction process is monitored in real time, and the problem of unclear dynamic reaction process is solved, and high sensitivity and stability detection of Cr(VI) in water is achieved, which improves the accuracy and reliability of the analysis results.

CN119897131APending Publication Date: 2025-04-29Hefei Comprehensive Science Center Environmental Research Institute
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510028604.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing electrochemical detection methods are difficult to accurately describe the dynamic changes in material structure and the real electrochemical reaction process in the problem that the dynamic reaction process is unclear and the analysis results are easily affected by experimental conditions.

Method used

In situ XAFS-electrochemical combined technology is used, combined with Pd-Cu diatom catalysts, and the active structure and reaction sites of sensitive materials are monitored in real time, revealing their dynamic changes at different reaction stages.

Benefits of technology

High sensitivity and stability detection of Cr(VI) in water is achieved, with a detection sensitivity of up to 0.50μA/ppb and a detection limit of 0.6ppb, improving the accuracy and reliability of the analysis results.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119897131A_ABST
    Figure CN119897131A_ABST
Patent Text Reader

Abstract

The invention discloses a Pd-Cu diatomic catalyst and a preparation method and application thereof, and the preparation method comprises the following steps: adding tetraammine palladium dichloride monohydrate, copper chloride and hydroxylamine hydrochloride into deionized water or pure water, and stirring to form a uniform mixed solution; slowly pouring into a uniform suspension formed by dispersing glucose in an ethanol solution, and heating and evaporating to obtain a precursor; and grinding into powder, and calcining in a protective atmosphere to obtain the catalyst. An analysis method based on an in-situ XAFS-electrochemical coupling technology is adopted, and it is verified that the Pd-Cu diatomic catalyst prepared through the method can detect Cr (VI) in water with high sensitivity and stability. The detection sensitivity is up to 0.50 mu A / ppb, the detection limit is 0.6 ppb, and the method has a huge application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electroanalytical sensing, and specifically relates to a Pd-Cu diatomic catalyst and a preparation method and application thereof. Background Art

[0002] Hexavalent chromium ion (Cr(VI)) is a typical persistent and highly toxic pollutant. It is easily soluble in water and combines with oxygen anions. It has serious teratogenic and mutagenic properties, which seriously endangers human health and the ecological environment. Accurate and efficient detection of Cr(VI) in water environment is crucial for timely warning, governance, control and elimination of Cr(VI) pollution in water environment.

[0003] The electroanalytical method has the unique advantages of simple operation, portable equipment, rapid response, and no need for pretreatment. It is one of the most promising technologies for on-site detection and long-term monitoring and assessment of Cr(VI) pollution risks. Electrocatalytic detection of Cr(VI) is mainly carried out in strong acid electrolytes because its reduction reaction requires 7 H + Involvement requires that the sensitive materials have high acid resistance and structural stability. In addition, there is still a huge challenge in quickly and efficiently breaking several Cr-O bonds to reduce Cr(VI) to Cr(III), a process that often relies on highly active precious metal-based catalytic sensitive materials. Such harsh reaction conditions and low Cr(VI) reduction efficiency place high demands on the stability and activity of sensitive materials. Therefore, designing highly active and highly stable sensitive materials is crucial to achieve highly sensitive and stable detection of Cr(VI).

[0004] In recent years, various nanomaterials have been used as sensitive materials to enhance the detection performance of heavy metals, such as precious metals, oxides, carbon materials, single-atom materials, metal nanoclusters, etc. In pursuit of optimizing and improving the detection performance of sensitive materials, researchers have adopted a variety of strategies, such as crystal phase / plane regulation, defect doping and surface modification, etc. The core of these studies lies in the precise identification of active sites of sensitive materials and the in-depth understanding of electrochemical reaction mechanisms.

[0005] However, current research methods still have some limitations, especially in exploring the sensitive mechanism of electroanalysis and the interaction between materials and targets. First, existing research mainly relies on non-in situ experimental techniques, which can only reveal the difference between the initial and final states of sensitive materials before and after electrochemical reactions, but lack a clear understanding of the dynamic reactions during electroanalysis. Secondly, the active structure and reaction sites of sensitive materials are easily affected by changes in various reaction conditions under actual experimental conditions, which will lead to deviations between the analysis results we obtain and the actual dynamic reaction process, making it difficult to accurately describe the dynamic changes of the material structure and the real electrochemical reaction process. Therefore, exploring the changes in the microscopic active structure of sensitive materials and revealing the corresponding catalytic sensitive mechanism are of great research significance for guiding the design of new sensitive materials and scientifically understanding the real electrochemical reaction process.

[0006] X-ray absorption fine structure spectroscopy (XAFS) can be tested at room temperature, normal pressure and in an air environment. It can provide the local geometric structure and electronic structure of solid, liquid and gas samples without considering the form of the sample. It can track the structural changes of nanomaterials in situ and provide information such as the type of coordinated atoms, bond length, coordination number, and electronic structure of the central absorbing atom. It can reveal the interaction mechanism between the target object and the material at the atomic level.

[0007] In view of the problems existing in current electrochemical detection methods, such as unclear dynamic reaction processes and analytical results being easily affected by experimental conditions, electrochemical detection methods can be organically cross-combined with XAFS technology to develop in-situ XAFS-electrochemical coupling technology, thereby helping to clarify the true reaction process and obtain more comprehensive and accurate analysis results. After the combination, the structural evolution process of the target and sensitive materials can be captured in real time and dynamically during the electrochemical analysis process, thereby providing information on the microscopic atomic and electronic structure changes of the target and sensitive materials at each reaction stage. Specifically, in-situ XAFS technology can monitor the active structure and reaction sites of sensitive materials in real time during the electrochemical reaction process, revealing their dynamic changes at different reaction stages. This capability not only helps us clarify the true electrochemical reaction path and catalytic sensitive mechanism, but also accurately identify the true active sites of the material. This has important theoretical support and guiding significance for the design and optimization of new sensitive materials with specific functions.

[0008] In addition, in-situ XAFS-electrochemical coupling technology can also improve the accuracy and reliability of analytical results. Since XAFS technology can be tested at room temperature, pressure and air environment, it can more realistically simulate actual reaction conditions, thereby avoiding analytical result deviations caused by changes in experimental conditions. Summary of the invention

[0009] Therefore, the purpose of the present invention is to provide a Pd-Cu diatomic catalyst and its preparation method and application. In addition, the present invention adopts an analysis method based on in-situ XAFS-electrochemical coupling technology to verify that the Pd-Cu diatomic catalyst prepared by the present invention can detect Cr(VI) in water with high sensitivity and stability. The specific technical scheme of the present invention is as follows:

[0010] The first object of the present invention is to provide a method for preparing a Pd-Cu diatomic catalyst, which comprises the following steps:

[0011] S11, adding tetraamminepalladium dichloride monohydrate, copper chloride and hydroxylamine hydrochloride into deionized water or pure water, and stirring to form a uniform mixed solution A;

[0012] S12, dispersing glucose in the ethanol solution to form a uniform suspension B;

[0013] S13, slowly pouring the mixed solution A into the suspension solution B, mixing thoroughly and then heating and evaporating to obtain a precursor;

[0014] S14, grinding the precursor into powder and calcining it under a protective atmosphere, grinding the obtained solid powder evenly and activating it, and then washing and drying it to obtain the Pd-Cu diatomic catalyst.

[0015] In a further embodiment, in step S11, the mass ratio of tetraamminepalladium dichlorohydrate, copper chloride and hydroxylamine hydrochloride is 2.97-5.94:3.54-7.80:1000-2000.

[0016] In a further embodiment, in step S12, the concentration of suspension B is 3.6-7.2 mg / mL.

[0017] In a further embodiment, in step S13, heating to evaporate is performed in an oven at 70-80°C to dryness.

[0018] In a further embodiment, in step S13, the volume ratio of the mixed solution A to the suspension B is 1-2:1-2.

[0019] In a further embodiment, in step S14, the protective atmosphere is nitrogen, the calcination temperature is 600-800° C., and the calcination time is 2-4 h;

[0020] The activation refers to soaking the ground solid powder in an acid solution for 8-10 hours; the acid solution includes a 1M sulfuric acid, hydrochloric acid or nitric acid solution.

[0021] The second object of the present invention is to provide a Pd-Cu diatomic catalyst prepared by the above preparation method.

[0022] The third inventive object of the present invention is to provide an application of the above-mentioned Pd-Cu diatomic catalyst, which is used to detect Cr(VI) in water, with a detection limit of 0.6 ppb and a detection sensitivity of up to 0.50 μA / ppb.

[0023] Further scheme, the steps of detecting Cr(VI) in water are as follows:

[0024] S21, ultrasonically dispersing the Pd-Cu diatomic catalyst in deionized water to form a uniform suspension;

[0025] S22, applying the suspension droplets on the surface of the electrode substrate to obtain a working electrode;

[0026] S23. Construct an in situ XAFS-electrochemical coupling platform to detect Cr(VI) in water.

[0027] In a further embodiment, in step S21, the concentration of the suspension is 0.6 mg / ml;

[0028] In step S22, the electrode substrate is a carbon paper electrode;

[0029] In step S23, the working electrode, the reference electrode and the counter electrode are used to construct an electrochemical three-electrode system; the carbon cloth is used as a conductor to connect the working electrode to a constant potential instrument to transmit current.

[0030] The advantages of the present invention are:

[0031] 1. The Pd-Cu diatomic catalyst prepared by the present invention is used as a sensitive material, which has excellent structural stability and ultra-high catalytic activity in a strongly acidic electrolyte, and exhibits highly sensitive and stable detection of Cr(VI) at a low overpotential, with a detection sensitivity of up to 0.50 μA / ppb and a detection limit of 0.6 ppb, which is far lower than the standard of no more than 50 ppb in drinking water stipulated by the World Health Organization, and has great practical application prospects.

[0032] 2. The dynamic "spring effect" of the Cu-Pd bond and the Cu-N bond in the Pd-Cu diatomic catalyst prepared by the present invention is that the Cu-Pd bond and the Cu-N bond are reversibly stretched under different voltage driving and restored and regenerated at a voltage of 0.6 V. Its dynamic "spring effect" greatly increases the structural stability of the material under applied voltage and the high reactivity in strong acid electrolytes, thereby effectively accelerating the reduction reaction of Cr(VI).

[0033] 3. The present invention expands the application of in-situ XAFS spectroscopy technology in the field of electroanalytical detection and develops in-situ XAFS-electrochemical coupling technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1This is a structural characterization of the Pd-Cu diatomic catalyst prepared in Example 1 of the present invention, wherein a is a scanning electron microscope image (SEM), b is a transmission electron microscope image (TEM), c is an element mapping image; d is a spherical aberration electron microscope image (HAADF-STEM);

[0035] Figure 2 EXAFS and XANES spectra prepared in Example 1 of the present invention, wherein a is the normalized Pd K-edge X-ray absorption near-edge structure (XANES) spectrum, b is the normalized Cu K-edge XANES spectrum, c and d are the extended X-ray absorption fine structure (EXAFS) spectra of Pd K-edge and Cu K-edge after Fourier transformation, respectively;

[0036] Figure 3 is an electrochemical detection current signal, wherein: a is a curve of the reduction current signal of the working electrode modified with the Pd-Cu diatomic catalyst prepared in Example 1 as a function of voltage, and d is a linear calibration curve of the relationship between the corresponding peak current value in a and the Cr(VI) concentration; b is a curve of the reduction current signal of the working electrode modified with the Pd SAC catalyst prepared in Comparative Example 1 as a function of voltage, and e is a linear calibration curve of the relationship between the corresponding peak current value in b and the Cr(VI) concentration; c is a curve of the reduction current signal of the working electrode modified with the Cu SAC catalyst prepared in Comparative Example 2 as a function of voltage, and f is a linear calibration curve of the relationship between the corresponding peak current value in c and the Cr(VI) concentration;

[0037] Figure 4 The detection stability of electrodes modified with Pd-Cu diatomic catalysts and Pd and Cu single-atom catalysts for a specific concentration of Cr(VI); wherein a is the detection stability of the working electrode modified with Pd-Cu diatomic catalysts prepared in Example 1 for Cr(VI), b is the detection stability of the working electrode modified with Pd SAC catalysts prepared in Comparative Example 1 for Cr(VI), and c is the detection stability of the working electrode modified with Cu SAC catalysts prepared in Comparative Example 2 for Cr(VI);

[0038] Figure 5 Figure 1 is a series of in-situ XAFS data and analysis results collected at different voltages, as well as a schematic diagram of the material structure change, wherein a is the Cu K-edge extended X-ray absorption fine structure (EXAFS) spectrum of the Pd-Cu diatomic catalyst prepared in Example 1 after Fourier transformation at different applied voltages, b is a relationship diagram of the bond length and coordination number of the Cu-N / Cu-O path obtained by fitting the spectrum in a as a function of voltage, c is a relationship diagram of the bond length and coordination number of the Cu-Pd path obtained by fitting the spectrum in a as a function of voltage, and d is a schematic diagram of the change of the Cu atomic structure in the Pd-Cu diatomic catalyst prepared in Example 1 as a function of voltage. DETAILED DESCRIPTION

[0039] Embodiment 1:

[0040] 4.64 mg of tetraamminepalladium dichlorohydrate, 3.54 mg of copper chloride (98% by mass concentration) and 1380 mg of hydroxylamine hydrochloride (98.5%) were added to 80 mL of deionized water and stirred for 20 min to form a uniform mixed solution A;

[0041] Disperse 288 mg of glucose (mass concentration ≥ 99.5%) in 80 mL of ethanol solution to form a uniform suspension B;

[0042] Slowly pour the mixed solution A into the suspension solution B (volume ratio is 1:1), stir rapidly for 1 hour, and after fully mixing, dry in an oven at 70°C to completely evaporate the solvent to obtain a precursor;

[0043] The precursor was ground into powder, transferred to a porcelain boat and placed in a tube furnace, and calcined at 600°C for 4 hours (heating rate of 5°C / min) under a nitrogen atmosphere. After cooling to room temperature, the obtained solid powder was evenly ground and then immersed in 1M H2SO4 for 8 hours to remove impurity byproducts and activate metal atoms.

[0044] The sample was collected by centrifugation, washed several times with deionized water until neutral, and then dried in an oven at 60° C. to obtain a Pd-Cu diatomic catalyst (Pd-Cu DAC).

[0045] The Pd-Cu diatomic catalyst prepared in Example 1 was observed under a scanning electron microscope (SEM), a transmission electron microscope (TEM), and a high-angle annular dark field scanning transmission electron microscope (HAADF-STEM) with spherical aberration correction, and the Figure 1 The picture shown. Figure 1 It can be seen from the SEM image in a and the TEM image in b that the Pd-Cu diatomic catalyst exhibits a three-dimensional porous cross-linked structure; Figure 1 The element mapping image of c shows that the C, N, Pd, and Cu elements are evenly distributed in the material, and the substrate is a nitrogen-doped carbon material (NC). Figure 1 The HAADF-STEM image in the middle d shows a large number of brighter spots and slightly darker spots, among which the white ellipse shows that they always appear in pairs; the brighter white spots represent Pd atoms, and the slightly darker white spots represent Cu atoms, because the atomic number of Pd atoms is larger than that of Cu atoms, and they appear brighter under HAADF-STEM. This shows that most of the Pd and Cu atoms appear in pairs and are dispersed on the NC substrate.

[0046] The Pd-Cu diatomic catalyst prepared in Example 1 was characterized by X-ray absorption spectroscopy (XAFS) to determine its chemical state and atomic coordination information, such as Figure 2 As shown. From the normalized Pd K-edge X-ray absorption near-edge structure (XANES) spectrum (a), it can be found that the edge-front trend of the Pd K-edge in the Pd-Cu diatomic catalyst (Pd-Cu DAC) is close to that of PdO, which indicates that the average valence state of Pd atoms in Pd-CuDAC is close to +2. In the normalized XANES spectrum of Cu K-edge (b), it can be observed that the edge-front trend of the Cu K-edge XANES spectrum in the Pd-Cu DAC is between that of CuO and Cu2O, which indicates that the chemical valence of Cu atoms in the Pd-Cu DAC is between +1 and +2. The extended X-ray absorption fine structure (EXAFS) spectra of Pd K-edge and Cu K-edge after Fourier transformation are shown in Figure 2 In c and d. Figure 2 As shown in Figure 3c, the two main scattering signals of Pd in ​​Pd-Cu DAC appear at 1.50 and Pd-Pd metal bond scattering signal with metallic palladium There is a significant difference, indicating that there is no Pd-Pd metal bond in Pd-Cu DAC. The fitting analysis shows that the scattering distances are Pd-N and Pd-Cu scattering paths for the first and second shell coordination of Pd atoms in Pd-Cu DAC, with coordination numbers of 2.9 and 0.7, respectively, and bond lengths of 2.02 and like Figure 2 As shown in (d), in the Cu K-edge EXAFS spectrum, the two main scattering signals of Pd-CuDAC appear at 1.50 and The Cu-Cu scattering signal of copper metal appears at It is shown that there is no Cu-Cu metal bond in Pd-Cu DAC. The fitting analysis shows that the Cu atom of Pd-Cu DAC is coordinated with 2.8 N atoms and 0.6 Pd atoms on average, and their bond lengths are (Cu-N) and (Cu-Pd). Pd-Cu and Cu-Pd scattering paths can be detected in both Pd and Cu K-edge EXAFS spectra, indicating that Pd-Cu metallic bonds are formed in the Pd-Cu DAC. Pd-Cu atoms mostly appear in pairs, and their average coordination structure is PdN3-CuN3. Therefore, a Pd-Cu diatomic catalyst with a coordination structure of PdN3-CuN3 was successfully synthesized on a nitrogen-doped carbon substrate, in which the average valence state of Pd atoms is about +2, and the valence state of Cu atoms is between +1 and +2.

[0047] Embodiment 2:

[0048] 5.94 mg of tetraamminepalladium dichlorohydrate, 7.80 mg of copper chloride (mass concentration 98%) and 2000 mg of hydroxylamine hydrochloride (98.5%) were added to 160 mL of pure water and stirred for 20 min to form a uniform mixed solution A;

[0049] Disperse 576 mg of glucose (mass concentration ≥ 99.5%) in 80 mL of ethanol solution to form a uniform suspension B;

[0050] Slowly pour the mixed solution A into the suspension solution B (volume ratio is 2:1), stir rapidly for 1 hour, and after fully mixing, dry in an oven at 70°C to completely evaporate the solvent to obtain a precursor;

[0051] The precursor was ground into powder, transferred to a porcelain boat and placed in a tube furnace, and calcined at 700°C for 3h (heating rate of 5°C / min) under a nitrogen atmosphere. After cooling to room temperature, the obtained solid powder was evenly ground and then immersed in 1M H2SO4 for 8h to remove impurity byproducts and activate metal atoms.

[0052] Embodiment 3:

[0053] 2.97 mg of tetraamminepalladium dichlorohydrate, 5.90 mg of copper chloride (98% by mass) and 1000 mg of hydroxylamine hydrochloride (98.5%) were added to 80 mL of deionized water and stirred for 20 min to form a uniform mixed solution A;

[0054] Disperse 428 mg of glucose (mass concentration ≥ 99.5%) in 160 ml of ethanol solution to form a uniform suspension B;

[0055] Slowly pour the mixed solution A into the suspension solution B (volume ratio is 1:2), stir rapidly for 1 hour, and after fully mixing, dry in an oven at 80°C to completely evaporate the solvent to obtain a precursor;

[0056] The precursor was ground into powder, transferred to a porcelain boat and placed in a tube furnace, and calcined at 800°C for 2h (heating rate of 5°C / min) under a nitrogen atmosphere. After cooling to room temperature, the obtained solid powder was evenly ground and then immersed in 1M H2SO4 for 8h to remove impurity byproducts and activate metal atoms.

[0057] The sample was collected by centrifugation, washed several times with deionized water until neutral, and then dried in an oven at 60° C. to obtain a Pd-Cu diatomic catalyst (Pd-Cu DAC).

[0058] Comparative Example 1:

[0059] 11.56 mg of dichlorotetraamminepalladium monohydrate and 1380 mg of hydroxylamine hydrochloride (98.5%) were added to 80 mL of deionized water and stirred for 20 min to form a uniform mixed solution A;

[0060] Disperse 288 mg of glucose (mass concentration ≥ 99.5%) in 80 mL of ethanol solution to form a uniform suspension B;

[0061] Slowly pour the mixed solution A into the suspension solution B, stir rapidly for 1 hour, and after fully mixing, dry in an oven at 70°C to completely evaporate the solvent to obtain a precursor;

[0062] The precursor was ground into powder, transferred to a porcelain boat and placed in a tube furnace, and calcined at 600°C for 4 hours (heating rate of 5°C / min) under a nitrogen atmosphere. After cooling to room temperature, the obtained solid powder was evenly ground and then immersed in 1M H2SO4 for 8 hours to remove impurity byproducts and activate metal atoms.

[0063] The sample was collected by centrifugation, washed several times with deionized water until neutral, and then dried in an oven at 60° C. to obtain a Pd single atom catalyst (Pd SAC).

[0064] Comparative Example 2:

[0065] 5.9 mg of copper chloride (mass concentration 98%) and 1380 mg of hydroxylamine hydrochloride (98.5%) were added to 80 mL of deionized water and stirred for 20 min to form a uniform mixed solution A;

[0066] Disperse 288 mg of glucose (mass concentration ≥ 99.5%) in 80 mL of ethanol solution to form a uniform suspension B;

[0067] Slowly pour the mixed solution A into the suspension solution B, stir rapidly for 1 hour, and after fully mixing, dry in an oven at 70°C to completely evaporate the solvent to obtain a precursor;

[0068] The precursor was ground into powder, transferred to a porcelain boat and placed in a tube furnace, and calcined at 600°C for 4 hours (heating rate of 5°C / min) under a nitrogen atmosphere. After cooling to room temperature, the obtained solid powder was evenly ground and then immersed in 1M H2SO4 for 8 hours to remove impurity byproducts and activate metal atoms.

[0069] The sample was collected by centrifugation, washed with deionized water several times until neutral, and then dried in an oven at 60° C. to obtain a Cu single atom catalyst (Cu SAC).

[0070] Test example 1:

[0071] 3 mg of the Pd-Cu diatomic catalyst prepared in Example 1 was ultrasonically dispersed in 5 mL of deionized water to form a uniform suspension. Then, 8 μL of the suspension was evenly dripped on the working electrode surface (3 mm in diameter) of the screen-printed electrode (three-electrode system) using a pipette. After natural drying at room temperature for 12 h, a working electrode modified with the Pd-Cu dual catalyst was obtained.

[0072] The screen-printed electrode modified with Pd-Cu dual catalyst was connected to an electrochemical workstation, and an appropriate amount of concentrated sulfuric acid diluted with water to 0.5 M dilute sulfuric acid was used as the reaction electrolyte to provide enough hydrogen ions (H + ) participates in the reduction reaction of Cr(VI). Before the electrochemical test, N2 gas was introduced into the electrolyte for 20 min to expel dissolved oxygen.

[0073] Take 1 portion of the above reaction electrolyte and add appropriate amounts of Cr(VI) in sequence to gradually increase the concentration of Cr. Specifically, the concentrations of Cr(VI) are 0, 20, 40, 60, 80, 100, 120, 140, 160, 180, 200, 300, 400, and 500 ppb, respectively.

[0074] Using an electrochemical workstation, linear sweep voltammetry (LSV) was used to detect the electrochemical reduction of Cr(VI). First, the open circuit voltage was set as the enrichment voltage, and the pre-enrichment time was 200s. Only the capture and adsorption ability of the Pd-Cu diatomic catalyst for Cr(VI) was relied upon to accumulate Cr(VI) on the electrode surface. Immediately afterwards, a voltage varying continuously from 0.8V to -0.6V (vsAg / AgCl) was applied to the working electrode at a scan rate of 0.1V / s. At the same time, the reduction current signal (I) versus voltage (E) was recorded at different Cr(VI) concentrations. The integrated area of ​​the reduction current represents the amount of Cr(VI) that participates in the electrochemical reduction reaction and is converted into Cr(III). Subsequently, a voltage of 0.6V was applied to the working electrode for 100s to regenerate the sensitive material on the electrode surface.

[0075] As above, 3 mg of each Pd SAC and Cu SAC catalyst prepared in Comparative Examples 1 and 2 were ultrasonically dispersed in 5 mL of deionized water to form a uniform suspension. Then, 8 μL of the above suspension was evenly drop-coated on the working electrode surface (3 mm in diameter) of the screen-printed electrode (three-electrode system) with a pipette. After drying naturally for 12 h at room temperature, the modified Pd and Cu working electrodes were obtained, and Cr (VI) was detected as above, wherein the electrolyte was a 0.5 M dilute sulfuric acid solution, and the concentration range of Cr (VI) detected was 100-1000 ppb and 100-1200 ppb, respectively, and the detection sensitivity was 0.025 μA / ppb and 0.037 μA / ppb (0.025 μA / ppb high concentration), respectively, and the detection limits were 56 and 67 ppb, respectively.

[0076] Test results such as Figure 3 As shown, Figure 3 In the figure a, the reduction current signal of Cr(VI) appears at 0.20V (vsAg / AgCl), and then the absolute value of the peak current signal gradually increases with the increase of Cr(VI) concentration. In addition, Figure 3 The graph (d) in the figure shows the relationship between the peak current intensity and the Cr(VI) concentration. It can be clearly observed that the absolute value of the peak current increases almost linearly with the increase of the Cr(VI) concentration, and the slope of the fitted linear equation represents the sensitivity of the detection.

[0077] It can be seen from the figure that the detection sensitivity of the electrode modified by Pd-Cu DAC prepared by the present invention to Cr(VI) is as high as 0.50μA / ppb, which is 1-2 orders of magnitude higher than the detection sensitivity of most sensitive electrodes reported so far, indicating that Pd-CuDAC has excellent ability to catalyze the reduction of Cr(VI). At the same time, the theoretical detection limit calculated by the 3σ method is 0.6ppb, which is far lower than the standard of Cr(VI) content in drinking water stipulated by the World Health Organization that does not exceed 50ppb.

[0078] Test example 2:

[0079] The same as test example 1, except that only 200 ppb Cr(VI) was added to the 0.5 M electrolyte for electrochemical stability test, the operation was repeated ten times, and ten response signals were measured.

[0080] Similarly, the Pd SAC and Cu SAC catalyst modified working electrodes prepared in Comparative Examples 1 and 2 were used to detect the electrochemical stability of adding 100 ppb Cr(VI) into 0.5 M electrolyte, and the operation was repeated ten times to measure ten response signals.

[0081] Test results such as Figure 4As shown in a, it can be seen that in ten stability tests, the peak shape, absolute value of peak current and peak position of the detection signal of 200 ppb Cr (VI) of the Pd-CuDAC modified electrode prepared by the present invention did not change significantly, and the standard deviation (RSD) of the ten peak currents was 2.68%, indicating that Pd-Cu DAC has excellent electrochemical stability for Cr (VI) catalytic detection. And b can be seen that in ten stability tests, the peak shape, absolute value of peak current and peak position of the detection signal of 1000 ppb Cr (VI) of the Pd SAC modified electrode did not change significantly, and the standard deviation (RSD) of the ten peak currents was 3.00%, indicating that Pd SAC has excellent electrochemical stability for Cr (VI) catalytic detection. From Figure 4 As can be seen in Figure c, in the ten stability tests, the detection signal of the Cu SAC-modified electrode for 1000 ppb Cr(VI) becomes broadened and the absolute value of the peak current continues to decrease as the number of cycle detections increases. The standard deviation (RSD) of the ten peak currents is 7.21%, indicating that the electrochemical stability of Cu SAC for catalytic detection of Cr(VI) is poor.

[0082] Embodiment 6:

[0083] In order to meet the requirements of both electrochemical testing and XAFS testing, 1.5*1.5 cm carbon paper was selected as the working electrode so that more catalysts can be loaded to obtain high-quality XAFS spectra.

[0084] The Pd-Cu diatomic catalyst prepared in Example 1 was ultrasonically dispersed in deionized water to form a uniform suspension. The suspension containing 10 mg of Pd-Cu DAC was evenly coated on the carbon paper electrode using a pipette to cover the entire carbon paper surface. After natural drying, the same operation was used for modification twice to ensure the uniformity and density of the carbon paper surface material to obtain a working electrode.

[0085] At the same time, the Ag / AgCl electrode was used as the reference electrode and the Pt wire electrode was used as the counter electrode to construct an electrochemical three-electrode system for electrochemical detection of Cr(VI). A 1*6cm carbon cloth strip was used as a conductor, and polyimide tape (Kapton) was used to tightly fit the carbon paper and the carbon cloth to ensure rapid and effective transfer of electrons, and the three-electrode system was connected to a constant potential instrument to transmit current.

[0086] The in-situ electrolytic cell was filled with 50 mL of 0.5 M dilute sulfuric acid as the electrolyte, and Cr(VI) was added to a concentration of 200 ppb.

[0087] The in-situ XAFS-electrochemical coupling platform was built. The Lyle-fluorescence mode was used to collect the XAFS spectra of Cu K edge (E0=8979eV) in Pd-CuDAC materials at different voltages (0.8~-0.6V) during the Cr(VI) electroanalysis process at the X-ray absorption spectral line station (1W1B) of the Beijing Synchrotron Radiation Facility. A fixed voltage was applied to the modified carbon paper electrode for 10 minutes at each voltage to obtain better high-quality spectral signals. The collected series of XAFS spectra were normalized and pre-processed using Athena software, and the processed data were fitted and analyzed using Artemis software to obtain the change information of the electronic structure and coordination structure around the Cu atom, so as to obtain the change information of the Pd-Cu DAC structure. Figure 5 As shown in the EXAFS spectrum shown in a, it can be found that as the voltage decreases from 0.8V to 0.15V, the intensity and position of the two main scattering signals of the Cu-N / Cu-O path and the Cu-Pd path remain almost unchanged. Then, the intensity of these two scattering signals begins to decrease significantly below 0.1V, and continues to decrease as the voltage changes from 0.1V to -0.6V. Then, the above EXAFS spectra are fitted to obtain the changes in the scattering distance and coordination number of the Cu-N / Cu-O and Cu-Pd paths under different applied voltages, as shown in Figure 1. Figure 5 As shown in b and c, from 0.8V to 0.15V, the Cu-N / Cu-O path scattering distance has almost no significant change ( Figure 5 b), then as the voltage continues to decrease to -0.6 V, the Cu-N / Cu-O scattering path distance changes from Stretch to This is due to the negative reduction voltage causing the oxidation state of Cu atoms to decrease. At the same time, its coordination number begins to decrease at 0.1V, and the coordination number continues to decrease as the voltage decreases to -0.6V. The coordination number of the Cu-N / Cu-O path decreases from 4.2 to 3.0, which is due to the desorption and release of the coordinated O atoms in H2CrO4 from the adsorbed Cu atom surface, revealing the transformation process of H2CrO4 to Cr(III) ions under the reduction voltage. Similarly, in the voltage range of 0.8 to 0.15V, the scattering distance of the Cu-Pd path remains unchanged ( Figure 5 c), and then as the voltage drops from 0.1V to -0.6V, the bond length of Cu-Pd changes from Gradually stretch to The stretching of the Cu-Pd bond length is mainly caused by the reduction of the valence state of the Cu atom at -0.6V. It is worth noting that when a voltage of 0.6V is applied to the electrode after the in-situ experiment to regenerate the electrode surface material, the coordination number and bond length of the Cu-N / Cu-O path and the Cu-Pd path in the Pd-Cu DAC / Cr-refresh are basically the same as those in the Pd-Cu DAC / Cr before use, which proves that the evolution of the chemical structure of Cu atoms has excellent reversibility with voltage changes. That is, driven by voltage, the change in the microscopic coordination structure of Cu atoms is completely reversible. In the electrochemical reduction reaction of Cr(VI), the reversible stretching and recovery of Cu-Pd bonds and Cu-N bonds driven by different voltages is defined as a dynamic "spring effect". The structural schematic diagram corresponding to the "spring effect" of the voltage-driven Pd-Cu DAC structural evolution is shown in the figure. Figure 5 As shown in middle d.

[0088] Therefore, the combination of electrochemical tests and in situ XAFS spectroscopy demonstrated that the Cu-N and Cu-Pd bonds in Pd-Cu DAC can reversibly stretch and recover under the drive of different voltages during the reduction of Cr(VI) to Cr(III). The reversible structural evolution of this dynamic "spring effect" of Pd-Cu DAC ensures that the Cu atoms can maintain excellent structural stability and electrochemical stability as well as ultra-high catalytic activity for Cr(VI) during electrochemical cycling tests.

[0089] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a Pd-Cu diatomic catalyst, characterized in that: The following steps are involved: S11, adding tetraamminepalladium dichloride monohydrate, copper chloride and hydroxylamine hydrochloride into deionized water or pure water, and stirring to form a uniform mixed solution A; S12, dispersing glucose in the ethanol solution to form a uniform suspension B; S13, slowly pouring the mixed solution A into the suspension solution B, mixing thoroughly and then heating and evaporating to obtain a precursor; S14, grinding the precursor into powder and calcining it under a protective atmosphere, grinding the obtained solid powder evenly and activating it, and then washing and drying it to obtain the Pd-Cu diatomic catalyst.

2. The preparation method according to claim 1, characterized in that: In step S11, the mass ratio of dichlorotetraamminepalladium monohydrate, copper chloride and hydroxylamine hydrochloride is 2.97-5.94:3.54-7.80:1000-2000.

3. The preparation method according to claim 1, characterized in that: In step S12, the concentration of suspension B is 3.6-7.2 mg / mL.

4. The preparation method according to claim 1, characterized in that: In step S13, heating to evaporate is performed by using an oven at 70-80°C to dry.

5. The preparation method according to claim 1, characterized in that: In step S13, the volume ratio of the mixed solution A to the suspension B is 1-2:1-2.

6. The preparation method according to claim 1, characterized in that: In step S14, the protective atmosphere is nitrogen, the calcination temperature is 600-800°C, and the time is 2-4h; The activation refers to soaking the ground solid powder in an acid solution for 8-10 hours; the acid solution includes a 1M sulfuric acid, hydrochloric acid or nitric acid solution.

7. The Pd-Cu diatomic catalyst prepared by the preparation method according to any one of claims 1 to 6.

8. The use of the Pd-Cu diatomic catalyst as claimed in claim 7, characterized in that: Used to detect Cr(VI) in water, its detection limit is 0.6ppb and the detection sensitivity is as high as 0.50μA / ppb.

9. The use according to claim 8, characterized in that: The steps for detecting Cr(VI) in water are as follows: S21, ultrasonically dispersing the Pd-Cu diatomic catalyst in deionized water to form a uniform suspension; S22, applying the suspension droplets on the surface of the electrode substrate to obtain a working electrode; S23. Construct an in situ XAFS-electrochemical coupling platform to detect Cr(VI) in water.

10. The use according to claim 9, characterized in that: In step S21, the concentration of the suspension is 0.6 mg / ml; In step S22, the electrode substrate is a carbon paper electrode; In step S23, the working electrode, the reference electrode and the counter electrode are used to construct an electrochemical three-electrode system; the carbon cloth is used as a conductor to connect the working electrode to a constant potential instrument to transmit current.